Modeling Multiple-event Catastrophe Bond Prices Involving the Trigger Event Correlation, Interest, and Inflation Rates - Sukono; Riza Andrian Ibrahim; Moch Panji Agung Saputra; Yuyun Hidayat; Hafizan Juahir; Igif Gimin Prihanto; Nurfadhlina Binti Abdul Halim (MDPI, 2024)
Indexed by WOS/ Scopus